Cytotoxic, genotoxic, and oxidative stress-inducing effect of an L-amino acid oxidase isolated from Bothrops jararacussu venom in a co-culture model of HepG2 and HUVEC cells - Machado, A. R.T.; Aissa, A. F.; Ribeiro, D. L.; Costa, T. R.; Ferreira, R. S. [UNESP]; Sampaio, S. V.; Antunes, L. M.G. (Elsevier, 2019)
Hepatocellular carcinoma incidence rates have increased worldwide, which encouraged the development of new chemotherapeutic drugs. L-Amino acid oxidases from snake venoms are cytotoxic towards human tumor cells in in vitro monoculture systems, which do not simulate the tumor microenvironment. We examined the antitumor potential of BjussuLAAO-II, an L-amino acid oxidase from Bothrops jararacussu venom, in hepatocarcinoma cells (HepG2) in monoculture and co-culture with human umbilical vein endothelial cells (HUVEC) in vitro. All the concentrations tested (0.25–5.00 μg/mL) were cytotoxic (MTT and clonogenic survival assays) towards HepG2 and HUVEC cells in monoculture, and increased oxidative stress by 2′,7′-dichlorofluorescin diacetate fluorescence assay. Only 1.00 and 5.00 μg/mL exerted these effects in HepG2 cells co-cultured with HUVEC cells, and were genotoxic (comet assay) to HUVEC cells in monoculture. BjussuLAAO-II at 5.00 μg/mL induced DNA, but not chromosomal damage (micronucleus assay) in HepG2 cells in mono- and co-culture. The cytotoxicity and genotoxicity was more pronounced in monoculture, indicating that the tumor microenvironment influences the cellular response. BjussuLAAO-II caused cell death and DNA damage in HepG2 cells in vitro by inducing oxidative stress. Therefore, BjussuLAAO-II is a promising molecule for the development of new antitumor drugs.
Keywords: Micronucleus; Snake venom; Tumor microenvironment